Acute effects of right ventricular pacing on cardiac haemodynamics and transvalvular impedance - Taborsky, Milos; Fedorco, Marian; Skala, Tomas; Kocianova, Eva; Pastucha, Dalibor; Richter, David; Petrkova, Jana; Di Gregorio, Franco; Barbetta, Alberto; Vaclavik, Jan (Biomedical papers, 2014)
Aims: To assess the acute side-effects of right ventricular (RV) stimulation applied in apex and mid-septum, in order to establish the optimal lead location in clinical practice.Methods: During pacemaker implantation, the ventricular lead was temporarily fixed in the apex and then moved to mid-septum. In both positions, surface and endocardial electrograms and transvalvular impedance (32 cases), left ventricular (LV) pressure (23), and transthoracic echocardiography (10) were acquired with intrinsic activity and VDD pacing.Results: A larger increase in QRS duration was noticed with apical than septal pacing (65 ± 25 vs. 45 ± 29 ms; P<10-4). The proportion of cases where RV stimulation affected the transvalvular impedance waveform was higher with apical lead location (56% vs. 20%; P<0.02). VDD pacing at either site reduced the maximum dP/dt by 6% with respect to intrinsic AV conduction (IAVC; P<0.005). The maximum pressure drop taking place in 100 ms was reduced by 6 and 8%, respectively, with apical and septal pacing (P<0.01 vs. IAVC). Apical VDD decreased mitral annulus velocity in early diastole (E') from 7.5 ± 1.4 to 5.9 ± 0.9 cm/s (P<0.02) and prolonged the E-wave deceleration time (DT) from 156 ± 33 to 199 ± 54 ms (P<0.02), while septal pacing induced non-significant modifications in E' and DT.Conclusion: Ventricular stimulation acutely impairs LV systolic and diastolic performance, independent of the pacing site. Septal lead location preserves RV contraction mechanics and reduces the electrical interventricular delay.
Keywords: apical pacing; septal pacing; QRS duration; LV pressure; transvalvular impedance; echocardiography